2006
DOI: 10.1158/0008-5472.can-05-4652
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Habitual Duration of Sleep and Incidence of Breast Cancer in a Large Cohort of Women

Abstract: Mounting evidence suggests habitual sleep duration is associated with various health outcomes; both short and long sleep duration have been implicated in increased risk of cardiovascular disease, diabetes, and all-cause mortality. However, data on the relation between sleep duration and cancer risk are sparse and inconclusive. A link between low levels of melatonin, a hormone closely related to sleep, and increased risk of breast cancer has recently been suggested but it is unclear whether duration of sleep ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 28 publications
7
93
4
Order By: Relevance
“…There have, however, been three observational studies of sleep duration and breast cancer risk (McElroy et al, 2006;Pinheiro et al, 2006). Among these, one reported a decreased risk in long sleepers (Verkasalo et al, 2005), the second reported no association (Pinheiro et al, 2006), whereas the third reported an increased risk in long sleepers (McElroy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have, however, been three observational studies of sleep duration and breast cancer risk (McElroy et al, 2006;Pinheiro et al, 2006). Among these, one reported a decreased risk in long sleepers (Verkasalo et al, 2005), the second reported no association (Pinheiro et al, 2006), whereas the third reported an increased risk in long sleepers (McElroy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There have, however, been three observational studies of sleep duration and breast cancer risk (McElroy et al, 2006;Pinheiro et al, 2006). Among these, one reported a decreased risk in long sleepers (Verkasalo et al, 2005), the second reported no association (Pinheiro et al, 2006), whereas the third reported an increased risk in long sleepers (McElroy et al, 2006). Among possible reasons for these differences from our findings (apart from the site of cancer), McElroy et al (2006) conducted a casecontrol study while Pinheiro et al (2006) studied residential nurses in the United States with rotating shift work and varying timing of sleep so that generalising from their results may be inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to melatonin secretion, there have been several observational studies on night work or visual impairment and breast cancer (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Schernhammer et al, 2001;Megdal et al, 2005;Pukkala et al, 2006;Schwartzbaum et al, 2007). In addition, there have been three prospective cohort studies of sleep duration and the risk of breast cancer, although with inconsistent findings (Verkasalo et al, 2005;Pinheiro et al, 2006;Wu et al, 2008).…”
mentioning
confidence: 99%
“…Dr. Sturgeon et al [4] now provide the sixth study on the issues concerned and report mixed results. Overall, with regard to how long one sleeps, first [4][5][6][7][8]-but not all [9]-epidemiological evidence could be viewed in line with increased cancer risks in those who sleep less than others [2].…”
Section: Introductionmentioning
confidence: 99%